2019
DOI: 10.7150/thno.34669
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-mediated cavitation enhances the delivery of an EGFR-targeting liposomal formulation designed for chemo-radionuclide therapy

Abstract: Nanomedicines allow active targeting of cancer for diagnostic and therapeutic applications through incorporation of multiple functional components. Frequently, however, clinical translation is hindered by poor intratumoural delivery and distribution. The application of physical stimuli to promote tumour uptake is a viable route to overcome this limitation. In this study, ultrasound-mediated cavitation of microbubbles was investigated as a mean of enhancing the delivery of a liposome designed for chemo-radionuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Understanding this process will be conducive to understanding the relationship between ubiquitination and EGFR‐associated tumours. Recently, targeted degradation of EGFR has been shown previously to induce cell death in EGFR overexpressing cancers . Furthermore, the application of EGFR degradation strategies may provide new ideas and experimental evidence for new pancreatic cancer treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding this process will be conducive to understanding the relationship between ubiquitination and EGFR‐associated tumours. Recently, targeted degradation of EGFR has been shown previously to induce cell death in EGFR overexpressing cancers . Furthermore, the application of EGFR degradation strategies may provide new ideas and experimental evidence for new pancreatic cancer treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies in this field applied the approach in two steps: Firstly, the skin would be exposed to ultrasound with or without gas-bubble cavitation nuclei to create pores, and then a second stage of drug application would be performed [ 272 , 273 ]. Whilst encouraging results were produced, the process was somewhat suboptimal and is hard to standardise for clinical practice.…”
Section: Vaccination Into the Dermal Compartment Without Needle Anmentioning
confidence: 99%
“…It has been shown that an acoustic radiation force can push targeted MBs toward the vessel wall during ultrasound molecular imaging and thereby promote the binding and retention of MBs in the diseased area [35,56]. Furthermore, ultrasound-induced cavitation, by increasing vessel permeability and generating convective flow, will enhance the extravasation of biochemical agents to the tumor [57]. In research using focused ultrasound with drug-loaded microbubbles for rat tumors, additional VEGFR2-targeting have been demonstrated significantly enhance drug release and reduce tumor progression in a rat model [58].…”
Section: Discussionmentioning
confidence: 99%